La séquence paléolithique de Karain E (Antalya, Turquie) : analyses techniques et typologiques (1989-2009) - Otte, Marcel, (Archaeopress Archaeology, 2020)
The long Paleolithic sequence of Karain (Antalya, Turkey) began around 500,000 years ago and continued until the final Paleolithic around 10,000 BC. This volume presents all the cultural and technical variations during this immense period, situated in a context which joins Africa, Asia, and Europe.